Pengukuran Karakteristik Lahan Berbasis Internet of Things - Lukie Perdanasari; Arvita Agus Kurniasari; Trismayanti Dwi Puspitasari; Bety Etikasari; Denny Trias Utomo; Jumiatun Jumiatun; Octavian Yudha Mahendra (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Climate change is one of the factors that affect crop production, so it is necessary to implement strategies and technologies to maintain the availability of cereal crops in Indonesia. It is necessary to prepare the land for the early planting process and monitoring plant growth in order to produce maximum crops. Utilization of the Internet of Things (IoT) can be used to monitor soil temperature and pH in real time, so hope for the long term it can increase crop production. The purpose of this research is to make a prototype design system with Internet of Things (IoT) technology to obtain temperature and pH data. This tool will test the functional accuracy. This research for measuring the characteristics of land based on IOT uses a prototype method consisting of Communication, Quick Plan, Modelling Quick Design, Construction of prototype, and Development Delivery & Feedback. Assembling the Wemos microcontroller, D1 R1, Breadboard, DS18B20 temperature sensor, 4700 Ohm Resistor, soil pH sensor, and 16x2 I2C LCD and connected using jumper cables with application control will be implemented into Wemos D1 R1 using the C++ programming language using Arduino IDE. Testing of the tool is carried out to ensure that the sensor is functionally able to read the temperature and pH of the soil correctly. Testing used black box method and was implemented in 5 land axis points at Politeknik Negeri Jember. The results used tools and litmus paper showed the same value. The conclusion and benefit of detecting land characteristics using the Wemos microcontroller showed more detailed measurement results with numbers behind the comma and a tool accuration rate of 100%.